Pengaruh latihan shooting dengan konsep beef terhadap kemampuan shooting free throw Pada ekstrakulikuler bola basket putra sman 1 kuok - Akbar Gani, Robby (Jurnal Inovasi Olahraga, 2024)
The problems found in this study include: 1) the ball rarely goes in when shooting, 2) students have not mastered the correct body position or basic attitude when shooting, 3) students cannot control the power of the throw, and 4) students' lack of enthusiasm in do a series of exercises. This study aims to determine the eﬀect of shooting practice with the concept of BEEF (X) on the ability to shoot free throw (Y) in men's basketball extracurricular at SMKN 1 KUOK. The method used in this study is an experimental method, with the research design used in this study is 'One-Group Pretest Posttest Design'. The population in this study were basketball extracurricular students at SMAN 1 KUOK, totaling 10 athletes. The instrument used in this research is Shooting Free Throw. Based on data analysis with the results: Pree-test average of 1.8 increased by 2.5 or 1.39% to 4.3 in Post-test with results (t count 6.76 > t table 1.833), then Ha is accepted . Thus, it can be concluded that shooting practice with the BEEF concept aﬀects the free throw shooting ability of male basketball extracurricular students at SMAN 1 KUOK. Keyword: Shooting Free Throw, BEEF, Extracuricular The problems found in this study include: 1) the ball rarely goes in when shooting, 2) students have not mastered the correct body position or basic attitude when shooting, 3) students cannot control the power of the throw, and 4) students' lack of enthusiasm in do a series of exercises. This study aims to determine the eﬀect of shooting practice with the concept of BEEF (X) on the ability to shoot free throw (Y) in men's basketball extracurricular at SMKN 1 KUOK. The method used in this study is an experimental method, with the research design used in this study is 'One-Group Pretest Posttest Design'. The population in this study were basketball extracurricular students at SMAN 1 KUOK, totaling 10 athletes. The instrument used in this research is Shooting Free Throw. Based on data analysis with the results: Pree-test average of 1.8 increased by 2.5 or 1.39% to 4.3 in Post-test with results (t count 6.76 > t table 1.833), then Ha is accepted . Thus, it can be concluded that shooting practice with the BEEF concept aﬀects the free throw shooting ability of male basketball extracurricular students at SMAN 1 KUOK. Keyword: Shooting Free Throw, BEEF, Extracuricular